Silicon nitride ceramic-based composite material and preparation method thereof
By introducing silica-coated modified boron nitride and resin composite phase change microcapsules into silicon nitride ceramics, and combining them with Si3N4-C@Al2O3 core-shell fiber aerogel, the problems of high brittleness and poor interfacial bonding of silicon nitride ceramics were solved, and the high strength and high temperature stability of the material were achieved.
Patent Information
- Application Number
- CN202511224304.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-12-05
AI Technical Summary
Silicon nitride ceramics are brittle and prone to cracking and fracture. The interfacial bonding between the reinforcing phase and the silicon nitride matrix is poor, which affects the mechanical properties and high-temperature resistance of the material.
A silica-coated modified boron nitride and resin composite phase change microcapsules are stably attached to the surface of Si3N4-C@Al2O3 core-shell fiber aerogel through chemical bonding and mechanical interlocking, which enhances the interfacial bonding strength. Furthermore, the fiber toughening, aerogel pores, and microcapsule stress dispersion improve fracture toughness and enhance high-temperature resistance.
It significantly improves the mechanical properties and high-temperature resistance of silicon nitride ceramics, enhances interfacial bonding strength, reduces the risk of phase separation, and improves fracture toughness and high-temperature stability.
Smart Images

Figure CN121063944A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of silicon nitride ceramics, and particularly relates to a silicon nitride ceramic matrix composite material and a preparation method thereof. BACKGROUND
[0002] Silicon nitride ceramics have excellent comprehensive performance, and the characteristics include high hardness, good wear resistance, excellent chemical corrosion resistance and good thermal shock resistance; in the electrical and microelectronic fields, silicon nitride is often used as an insulating medium layer, a passivation layer, an optical filter and an optical signal transmitter in integrated circuits, and is widely used for manufacturing corrosion-resistant and wear-resistant parts in the chemical and chemical fields, in addition, silicon nitride ceramics can be made into crucible products for use in metal smelting, prolonging the service life of the crucible, improving the smelting efficiency and safety, and can be used as biological bone material in the biological medical field, therefore, silicon nitride ceramic materials show broad application prospects in many important fields; in order to further optimize the performance of the material and expand the use field, a composite material can be formed by introducing a reinforcing phase (such as fiber, whisker, particle, etc.) into the silicon nitride matrix, which has the excellent performance of silicon nitride ceramics and the designability of the composite material.
[0003] The existing technology mainly has the following problems:
[0004] Silicon nitride has the disadvantage of large brittleness, and is prone to crack and fracture, at the same time, the interface bonding between the added reinforcing phase and the silicon nitride matrix is poor, which also affects the mechanical properties, high temperature resistance and the like of the material. SUMMARY
[0005] In view of the above situation, in order to overcome the defects of the prior art, the application provides a silicon nitride ceramic matrix composite material, which comprises the following components in parts by weight: silicon dioxide coated modified boron nitride and resin composite phase change microcapsules 10-15 parts, Si3N4-C@Al2O3 core-shell fiber aerogel 50-60 parts, nano yttrium oxide 8-10 parts, and polyvinyl butyral 5-8 parts.
[0006] The silicon dioxide coated modified boron nitride and resin composite phase change microcapsules are made of the following components in parts by weight: hydroxylated boron nitride 2-6 parts, pentaerythritol paraffin blend 30-40 parts, resin prepolymer solution 10-20 parts, compound emulsifier 8-10 parts, silicon dioxide sol 3-5 parts, hydrogen peroxide 5-8 parts, and 3-glycidyl ether oxypropyl trimethoxysilane 1-3 parts.
[0007] The preparation method of the silicon dioxide coated modified boron nitride and resin composite phase change microcapsules specifically includes the following steps:
[0008] (1) Put 8.0-10.0 g boron nitride and 4.0-5.0 g glucose into a ball milling jar, the ratio of material to ball is 1:5, fix the ball milling jar in a planetary ball mill, ball mill at 400-500 rpm for 10-12 h, put the ball milling product into deionized water, ultrasonic dispersion at 200-400 W for 20-30 min, first centrifuge at low speed of 1000-2000 rpm for 5-10 min, then centrifuge at high speed of 9000-10000 rpm for 10-20 min, collect the precipitate, perform suction filtration, ethanol washing, and vacuum freeze-drying, the hydroxylated boron nitride has hydrophilic groups on the surface, which can be better dispersed in water or polar solvents, avoiding the agglomeration problem of traditional boron nitride in ceramic slurry, the uniform dispersion of the hydroxylated boron nitride sheet layer can hinder crack propagation, improve the fracture toughness of the ceramic through crack deflection and bridging mechanism, and also more easily form a heat conduction network in the ceramic to improve the high temperature resistance, and obtain hydroxylated boron nitride;
[0009] (2) Add 0.8-1.0 g melamine, 1.0-2.0 g urea, and 2.0-3.0 g formaldehyde solution to 30 mL deionized water, adjust the pH to 8.0-8.5 using a 5% mass fraction triethanolamine solution, stir at 60-70°C for 40-50 min to obtain a resin prepolymer solution, dissolve 1-3 mL 3-glycidyloxypropyltrimethoxysilane in 15 mL 50-70% mass fraction ethanol solution, adjust the pH to 5.0-6.0 with acetic acid, pre-hydrolyze for 20-30 min, then weigh 0.2-0.6 g hydroxylated boron nitride from step (1) into the hydrolysis solution, ultrasonic dispersion at 100-200 W for 10-20 min, adjust the pH to 8.5-9.0 with a 10% mass fraction triethanolamine solution, and finally add to the resin prepolymer solution, a high-performance resin prepolymer solution is prepared by modifying the hydroxylated boron nitride composite with melamine-urea-formaldehyde resin and silane coupling agent, the nanosheet structure of the hydroxylated boron nitride can form a reinforcing network in the resin, improving the mechanical strength of the composite material and reducing the dimensional change of the resin at high temperature, 3-glycidyloxypropyltrimethoxysilane enhances the interfacial bonding force between the hydroxylated boron nitride and the resin, reducing the risk of phase separation, and obtaining a resin prepolymer solution containing modified boron nitride;
[0010] (3) 3.0-4.0 g pentaerythritol paraffin blend, 0.8-1.0 g complex emulsifier and 30-50 mL deionized water were added into a 250 mL three-necked flask, the complex emulsifier was composed of Span 80 and Tween 60, the mass ratio of the two was 3:1, after completely melting at 50°C, the modified boron nitride-containing resin prepolymer solution in step (2) was added, and emulsification treatment was carried out at a speed of 15000-18000 rpm for 20-30 min, ice bath cooling treatment was adopted during the emulsification process, the obtained oil-in-water emulsion was transferred to a 500 mL three-necked flask, a 5% triethanolamine solution was added under the stirring speed of 300-400 rpm to adjust the pH to 8.5, 10-20 min later, a 10% citric acid solution was slowly added through a constant pressure dropping funnel to adjust the pH to 4.5-5.0, then the temperature was raised to 60°C at a rate of 0.5°C / min, 0.1-0.3 g sodium chloride was added, and the reaction was carried out for 0.5-1 h, then the temperature was raised to 80°C and the reaction was carried out for 1-2 h, finally the pH was adjusted to 7.0 by sodium hydroxide solution to terminate the reaction, the obtained suspension was sieved and suction filtered, and was washed with 60°C deionized water and anhydrous ethanol for 3-5 times, the precipitate was vacuum dried, the hydroxylated boron nitride embedded in the melamine-urea-formaldehyde co-condensation resin formed a dense thermosetting resin material, which was used as a wall material to coat the core material of the pentaerythritol paraffin blend, the hydroxylated boron nitride nanosheet formed a brick structure in the resin shell layer, when the crack propagated, the hydroxylated boron nitride sheet layer forced the crack to bypass or branch, at the same time, the plastic deformation of the resin could absorb energy, and the urea segment in the resin also provided flexibility, thus improving the risk of brittle fracture, the core material underwent phase change when the temperature changed, absorbing thermal stress, which also reduced the initiation of internal microcracks in the ceramic, the inert protection of the hydroxylated boron nitride and the synergistic effect of the resin carbonization network improved the high temperature stability of the ceramic material, and a modified boron nitride and resin composite phase change microcapsule was obtained;
[0011] (4) mixing 1-2 mL of tetraethyl orthosilicate and 7-8 mL of anhydrous ethanol, magnetically stirring for 10-20 min, then slowly adding 1-2 mL of deionized water and 0.05-0.1 mL of ammonia water, stirring in a 30-40℃ water bath for 1-2 h to obtain a silica sol for use, dispersing the modified boron nitride and resin composite phase change microcapsules in step (3) in 50 mL of 60℃ deionized water, adding 15% hydrogen peroxide liquid by mass fraction, ultrasonic treatment for 10-15 min, suction filtration, washing the product with anhydrous ethanol for 3-5 times, vacuum drying to obtain modified boron nitride and resin composite phase change microcapsule pretreatment powder for use, then dispersing the modified boron nitride and resin composite phase change microcapsule pretreatment powder in 50 mL of anhydrous ethanol, ultrasonic treatment for 20-30 min, then adding the silica sol to the dispersion liquid at a rate of 1 mL / min, while maintaining magnetic stirring at 30-35℃ and 800-1000 rpm for 10-12 h, finally centrifuging, washing the collected precipitate with anhydrous ethanol for 3-5 times, and supercritical CO2 drying, the oxidation pretreatment of the modified boron nitride and resin composite phase change microcapsule by hydrogen peroxide can ensure the stable loading of the silica coating layer deposited on the surface of the microcapsule, which is conducive to the coating layer to better improve the mechanical strength and chemical inertness of the microcapsule, and at the same time enhances the compatibility with the ceramic matrix, the structural characteristics of the microcapsule can locally plastically deform under stress, absorb impact energy, and improve the fracture toughness of the material, wherein the flexibility of the resin and the rigidity of the silica form a soft-hard alternating structure with a toughening effect, the high temperature resistance of the silica can isolate oxygen, prevent the decomposition of the resin at high temperature, and block the volatilization of paraffin, and the high thermal conductivity of the hydroxylated boron nitride can accelerate heat diffusion, avoid local overheating, and delay the high temperature oxidation of the ceramic matrix, to obtain a silica-coated modified boron nitride and resin composite phase change microcapsule;
[0012] Preferably, in step (3), the mass ratio of pentaerythritol and paraffin in the pentaerythritol-paraffin blend is 70:30, and the pentaerythritol, as a high melting point polyol, can enhance the skeleton support of paraffin and reduce the risk of deformation during the degreasing process, and the paraffin and pentaerythritol blend can widen the temperature control range of the ceramic material, and enhance the high temperature resistance as a phase change energy storage material for thermal performance regulation;
[0013] Preferably, in step (4), the amount of hydrogen peroxide liquid added is 3-5 mL, and the hydrogen peroxide can oxidize the organic matter remaining on the surface of the microcapsule, expose more hydroxyl groups, and enhance the interfacial bonding with the silica sol.
[0014] The application also provides a preparation method of a silicon nitride ceramic matrix composite material, specifically including the following steps:
[0015] S1, 2.0-2.5 g of polyacrylonitrile, 0.8-1.0 g of polysilazane, 0.3-0.4 g of basic aluminum acetate and 0.1-0.2 g of polyvinylpyrrolidone are dissolved in 10 mL of N,N-dimethylformamide solvent, stirred for 10-12 h to form a core layer solution for use, 0.5-1.0 g of polyvinylpyrrolidone is dissolved in 10 mL of 70% ethanol solution, stirred for 3-4 h, 0.3-0.5 g of 10-20 nm particle size of alumina particles is slowly added, first ultrasonic dispersion for 20-30 min at 200 W power, then aluminum nitrate nonahydrate is added, and then magnetic stirring is carried out for 3-4 h to form a shell layer solution for use. Then, using the coaxial electrospinning technology, the core layer solution is loaded into a 21G inner needle, and the shell layer solution is loaded into a 16G outer needle. The core layer solution has a pushing speed of 0.006-0.008 mL / min and a voltage of +16 kV to +18 kV, and the shell layer solution has a pushing speed of 0.01-0.02 mL / min and a voltage of -6 kV to -2 kV. The receiving distance is 18-20 cm. The prepared core-shell precursor nanofiber is collected in a 50-60°C oven for 0.5-1 h, then heated to 280-300°C at a rate of 5°C / min and kept for 2-3 h. The dried product is ground and dispersed in 50 mL of 50% ethanol solution, pre-frozen at -40°C for 1-2 h, then transferred to a liquid nitrogen environment at -196°C, and freeze-dried for 24-48 h. Finally, under Ar inert atmosphere, pretreatment at 500°C for 1-2 h, then heat treatment at 800-1000°C for 2-3 h. This process first forms a fiber structure with Si3N4-C as the core and alumina as the shell. The mechanical strength and high temperature resistance of the fiber are significantly better than that of a single fiber. When the crack encounters the core-shell fiber, it will deflect or be forced to bypass the fiber, consuming more energy. The alumina shell forms a dense oxide layer at high temperature, preventing oxygen from diffusing to the core layer and delaying the oxidation and decomposition of Si3N4. The core-shell fiber forms Si-O-Si or Si-O-Al covalent bonds at the contact points through freeze-drying and heat treatment, enhancing the stability of the aerogel. The Si3N4-C@Al2O3 core-shell fiber aerogel is obtained.
[0016] S2, grinding the Si3N4-C@Al2O3 core-shell fiber aerogel described in step S1 for 30-40s, and then adding the silica-coated modified boron nitride and resin composite phase change microcapsules, nano yttrium oxide into 100mL anhydrous ethanol, ultrasonic dispersion for 20-30min, adding polyvinyl butyral, stirring for 1-2h, freeze-drying, the obtained powder is loaded into a mold, cold pressing at 20-50MPa, isostatic pressing at 200-300MPa to shape, and then the embryo is treated at 300-600℃ for 1-2h in an Ar / N2 inert atmosphere, and then reacted at 1400-1600℃ for 2-3h, wherein the volume ratio of Ar and N2 is 9:1, the silica-coated modified boron nitride and resin composite phase change microcapsules are attached to the surface of the Si3N4-C@Al2O3 core-shell fiber aerogel, and are initially connected and fixed by van der Waals force and mechanical interlocking, the Si3N4-C@Al2O3 core-shell fiber aerogel serves as a matrix skeleton, and the silica-coated modified boron nitride and resin composite phase change microcapsules serve as a reinforcing phase, after sintering, the carbonized residues of the resin shell layer form chemical bonds with Si3N4 at the interface, further enhancing the interfacial bonding strength, reducing phase separation, polyvinyl butyral acts as a binder and forms a local coating film at the fiber-microcapsule interface, nano yttrium oxide reacts with Si3N4 and Al2O3 to form Y-Si-Al-O-N glass phase, filling the grain boundary pores and improving the density, to obtain a silicon nitride ceramic matrix composite material;
[0017] Preferably, in step S1, the amount of aluminum nitrate nine hydrate added is 0.1-0.2g, and the aluminum nitrate nine hydrate is decomposed at high temperature to generate active alumina, which together with the original nano alumina particles forms a ceramic phase, improving the uniformity and continuity of the shell layer, enhancing the mechanical strength and high temperature resistance, and also filling the fiber gap and forming a chemical bond with the core layer material through high temperature sintering, improving the bonding of the core-shell interface, effectively reducing stress concentration and improving toughness.
[0018] The beneficial effects obtained by the present application are as follows:
[0019] The application stabilizes the attachment of the silica-coated modified boron nitride and resin composite phase change microcapsules on the surface of the Si3N4-C@Al2O3 core-shell fiber aerogel in a chemical bonding and mechanical interlocking manner, enhances the interfacial bonding strength, reduces the risk of phase separation, better plays the combined action of both, improves the fracture toughness by fiber toughening, aerogel pores and microcapsule dispersed stress, improves the high temperature resistance by the low thermal conductivity of aerogel and the heat absorption effect of microcapsule, significantly improves the mechanical properties of silicon nitride in multiple ways, effectively enhances the high temperature resistance, and endows the silicon nitride ceramic matrix composite with excellent performance; in the silica-coated modified boron nitride and resin composite phase change microcapsules, the hydroxylated boron nitride is embedded in the melamine-urea-formaldehyde co-condensation resin as a dense thermosetting resin wall material, the core material of the pentaerythritol paraffin blend is coated first, then the modified boron nitride and resin composite phase change microcapsules are pretreated by hydrogen peroxide oxidation to ensure the stable loading of the silica coating layer deposited on the surface of the microcapsule, improve the mechanical strength and chemical inertness of the microcapsule, and the flexibility of the resin and the rigidity of the silica form a soft and hard alternating structure with a toughening effect, the high temperature resistance of the silica can isolate oxygen to prevent the decomposition of the resin and the volatilization of the paraffin, and the microcapsule can also locally plastically deform under stress to absorb impact energy and improve the fracture toughness of the material, the pentaerythritol paraffin blend core material undergoes phase change when the temperature changes, and absorbs thermal stress, wherein the inert protection of the hydroxylated boron nitride and the synergistic effect of the resin carbonization network also improve the high temperature stability of the material, the silica coating makes the surface of the microcapsule present nano concave-convex, and the mechanical combination with the ceramic substrate is increased; in the Si3N4-C@Al2O3 core-shell fiber aerogel, the three-dimensional network structure formed by the Si3N4-C@Al2O3 core-shell fiber absorbs the fracture energy through fiber pull-out, crack deflection and bridging effect, improves the fracture toughness of the silicon nitride material, at the same time, the high porosity of the aerogel can absorb impact energy, relieve external stress through pore wall deformation and fiber network elastic recovery, avoid brittle fracture, the porous structure of the aerogel can reduce heat conduction, and the open pores can also absorb thermal expansion stress to avoid cracking under high temperature cycling, furthermore, in the Si3N4-C@Al2O3 core-shell fiber, Si3N4 reacts with the shell Al2O3 to form Si-O-Al covalent bond, enhances the interfacial bonding, the coating of the shell Al2O3 consumes more fracture energy and improves the fracture toughness, and the alumina particles generated by the decomposition of aluminum nitrate nonahydrate prevent crack propagation through pinning effect and promote fiber pull-out work, and the shell can also form a dense oxide layer to effectively inhibit the oxidation of Si3N4 and improve the high temperature resistance; the application is a kind of silicon nitride ceramic matrix composite made of silica-coated modified boron nitride and resin composite phase change microcapsules, Si3N4-C@Al2O3 core-shell fiber aerogel, nano yttrium oxide and polyvinyl butyral, which improves the interfacial bonding of the reinforcing phase and the silicon nitride substrate, and improves the fracture toughness and high temperature resistance of the ceramic material. BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1 Scanning electron microscope image of the silicon nitride ceramic matrix composite prepared in Example 1 of the present application;
[0021] Figure 2 Fracture toughness result graph of Examples 1-4 and Comparative Examples 1-3 of the present application;
[0022] Figure 3 High temperature strength retention rate result graph of Examples 1-4 and Comparative Examples 1-3 of the present application. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. In addition, any method and material similar or equivalent to those described herein can be used in the present application. The preferred implementation methods and materials described herein are only used for demonstration, but cannot limit the content of the present application.
[0025] The experimental methods in the following embodiments are all conventional methods unless otherwise specified. The test materials used in the following embodiments are all purchased from commercial channels unless otherwise specified.
[0026] Example 1
[0027] The present embodiment proposes a silicon nitride ceramic matrix composite, which comprises the following components by weight: 15 parts of silicon dioxide coated modified boron nitride and resin composite phase change microcapsules, 60 parts of Si3N4-C@Al2O3 core-shell fiber aerogel, 10 parts of nano yttrium oxide, and 8 parts of polyvinyl butyral.
[0028] The silicon dioxide coated modified boron nitride and resin composite phase change microcapsules are made of the following components by weight: 6 parts of hydroxylated boron nitride, 40 parts of pentaerythritol paraffin blend, 20 parts of resin prepolymer solution, 10 parts of compound emulsifier, 5 parts of silica sol, 8 parts of hydrogen peroxide, and 3 parts of 3-glycidyl ether oxypropyl trimethoxysilane.
[0029] The preparation method of the silicon dioxide coated modified boron nitride and resin composite phase change microcapsules specifically comprises the following steps:
[0030] (1) Put 10.0 g of boron nitride and 5.0 g of glucose into a ball mill jar, with a material-to-ball ratio of 1:5, and fix the ball mill jar in a planetary ball mill, and mill at a speed of 500 rpm for 12 h. The ball-milled product is placed in deionized water, and ultrasonically dispersed at a power of 400 W for 30 min. First, centrifuge at a low speed of 2000 rpm for 10 min, and then centrifuge the upper clear liquid at a high speed of 10000 rpm for 20 min. Collect the precipitate, and perform suction filtration, ethanol washing, and vacuum freeze-drying. The hydroxylated boron nitride has a hydrophilic group on the surface, and can be better dispersed in water or a polar solvent, avoiding the agglomeration problem of traditional boron nitride in ceramic slurry. The uniform dispersion of the hydroxylated boron nitride sheet layer can hinder crack propagation, improve the fracture toughness of the ceramic through crack deflection and bridging mechanisms, and more easily form a heat-conducting network in the ceramic, improving the high-temperature resistance. Hydroxylated boron nitride is obtained;
[0031] (2) Add 1.0 g of melamine, 2.0 g of urea, and 3.0 g of formaldehyde solution to 30 mL of deionized water, adjust the pH to 8.5 using a 5% mass fraction of triethanolamine solution, and stir at 70°C for 50 min to obtain a resin prepolymer solution. Dissolve 3 mL of 3-glycidyloxypropyltrimethoxysilane in 15 mL of a 70% mass fraction of ethanol solution, adjust the pH to 6.0 with acetic acid, and pre-hydrolyze for 30 min. Then, weigh 0.6 g of the hydroxylated boron nitride obtained in step (1) into the hydrolysis solution, ultrasonically disperse at a power of 200 W for 20 min, adjust the pH to 9.0 with a 10% mass fraction of triethanolamine solution, and finally add to the resin prepolymer solution. A high-performance resin prepolymer solution is prepared by modifying the hydroxylated boron nitride with a melamine-urea-formaldehyde resin and a silane coupling agent. The nanosheet structure of the hydroxylated boron nitride can form a reinforcing network in the resin, improving the mechanical strength of the composite material and reducing the dimensional change of the resin at high temperatures. The 3-glycidyloxypropyltrimethoxysilane enhances the interfacial bonding force between the hydroxylated boron nitride and the resin, reducing the risk of phase separation. A resin prepolymer solution containing modified boron nitride is obtained;
[0032] (3) 4.0 g of pentaerythritol paraffin blend, 1.0 g of a compounded emulsifier, and 50 mL of deionized water were added to a 250 mL three-necked flask, the mass ratio of pentaerythritol and paraffin in the pentaerythritol paraffin blend was 70:30, pentaerythritol acted as a high-melting-point polyol and could enhance the skeleton support of paraffin, reducing the risk of deformation during the degreasing process, paraffin and pentaerythritol could widen the temperature control range of ceramic materials, and as phase change energy storage materials, they could enhance the high temperature resistance by regulating the thermal performance, the compounded emulsifier was composed of Span 80 and Tween 60, the mass ratio of the two was 3:1, after complete melting at 50°C, the resin prepolymer solution containing modified boron nitride in step (2) was added, and emulsification treatment was carried out at a speed of 18000 rpm for 30 min, ice bath cooling treatment was adopted during the emulsification process, the obtained oil-in-water emulsion was transferred to a 500 mL three-necked flask, a 5% triethanolamine solution was added under the stirring speed of 400 rpm to adjust the pH to 8.5, after 20 min, a 10% citric acid solution was slowly added through a constant pressure dropping funnel, the pH was adjusted to 5.0, then the temperature was raised to 60°C at a rate of 0.5°C / min, 0.3 g of sodium chloride was added, and the reaction was carried out for 1 h, then the temperature was raised to 80°C and the reaction was carried out for 2 h, finally, the pH was adjusted to 7.0 by sodium hydroxide solution to terminate the reaction, the obtained suspension was sieved and suction filtered, and then washed with 60°C deionized water and anhydrous ethanol for 5 times, respectively, the precipitate was vacuum dried, the hydroxylated boron nitride was embedded in the melamine-urea-formaldehyde co-condensation resin to form a dense thermosetting resin material as a wall material to coat the core material of the pentaerythritol paraffin blend, the hydroxylated boron nitride nanosheet formed a brick structure in the resin shell layer, when the crack propagated, the hydroxylated boron nitride sheet layer forced the crack to bypass or branch, at the same time, the plastic deformation of the resin could absorb energy, and the urea segment in the resin also provided flexibility, thus improving the risk of brittle fracture, the core material could absorb thermal stress when the temperature changed, and could also reduce the initiation of microcracks in the ceramic, the inert protection of the hydroxylated boron nitride and the synergistic effect of the resin carbonization network improved the high temperature stability of the ceramic material, and a modified boron nitride and resin composite phase change microcapsule was obtained;
[0033] (4) 2 mL of tetraethyl orthosilicate and 8 mL of anhydrous ethanol were mixed and magnetically stirred for 20 min, then 2 mL of deionized water and 0.1 mL of ammonia water were slowly added, and stirred at 40°C water bath for 2 h to obtain silica sol for standby. The modified boron nitride and resin composite phase change microcapsules described in step (3) were dispersed in 50 mL of 60°C deionized water, and 5 mL of 15% hydrogen peroxide liquid was added. Hydrogen peroxide can oxidize the residual organic matter on the surface of the microcapsules, exposing more hydroxyl groups and enhancing the interfacial bonding with the silica sol. Ultrasonic treatment for 15 min, suction filtration, the product was washed with anhydrous ethanol 5 times, vacuum drying, to obtain modified boron nitride and resin composite phase change microcapsule pretreatment powder, for standby, then the modified boron nitride and resin composite phase change microcapsule pretreatment powder was dispersed in 50 mL of anhydrous ethanol, and ultrasonic treatment for 30 min. Then the silica sol was added to the dispersion at a rate of 1 mL / min while maintaining magnetic stirring at 35°C and 1000 rpm for 12 h. Finally, centrifugation, the collected precipitate was washed with anhydrous ethanol 5 times, supercritical CO2 drying, hydrogen peroxide pretreatment of modified boron nitride and resin composite phase change microcapsules can ensure the stability of the silica coating layer deposited on the surface of the microcapsules, which is beneficial to the coating layer to better enhance the mechanical strength and chemical inertness of the microcapsules, and at the same time, enhance the compatibility with the ceramic matrix. The structural characteristics of the microcapsules can locally deform plastically under stress, absorbing impact energy and improving the fracture toughness of the material. The flexibility of the resin and the rigidity of the silica form a soft-hard alternating structure with toughening effect. The high temperature resistance of silica can isolate oxygen and prevent the decomposition of resin at high temperature, while blocking the volatilization of paraffin. The high thermal conductivity of hydroxylated boron nitride can accelerate heat diffusion, avoid local overheating, and delay the high temperature oxidation of the ceramic matrix. The silica-coated modified boron nitride and resin composite phase change microcapsules were obtained.
[0034] The embodiment provides a preparation method of a silicon nitride ceramic matrix composite material, specifically comprising the following steps:
[0035] S1, 2.5 g of polyacrylonitrile, 1.0 g of polysilazane, 0.4 g of basic aluminum acetate and 0.2 g of polyvinylpyrrolidone were dissolved in 10 mL of N,N-dimethylformamide solvent, stirred for 12 h to form a core layer solution for standby, 1.0 g of polyvinylpyrrolidone was dissolved in 10 mL of 70% ethanol solution, stirred for 4 h, 0.5 g of 10-20 nm particle size of alumina particles were slowly added, first ultrasonic dispersion for 30 min at 200 W power, then aluminum nitrate nonahydrate was added, the amount of aluminum nitrate nonahydrate added was 0.2 g, and the active alumina was generated by high temperature decomposition of aluminum nitrate nonahydrate, which together with the original nano-alumina particles formed a ceramic phase, which improved the uniformity, continuity, mechanical strength and high temperature resistance of the shell layer, and also filled the gap between the fibers, and formed a chemical bond with the core layer material through high temperature sintering, improved the bonding of the core-shell interface, effectively reduced stress concentration, and improved toughness, then magnetic stirring was carried out for 4 h to form a shell layer solution for standby, then a coaxial electrospinning technology was used, the core layer solution was filled into a 21G inner needle, and the shell layer solution was filled into a 16G outer needle, the core layer solution was pushed at a speed of 0.008 mL / min and a voltage of +18 kV, the shell layer solution was pushed at a speed of 0.02 mL / min and a voltage of -2 kV, the receiving distance was 20 cm, and the prepared core-shell precursor nanofiber was collected in a 60℃ oven for 1 h, then the temperature was increased to 300℃ at a rate of 5℃ / min and kept for 3 h, the dried product was ground and dispersed in 50 mL of 50% ethanol solution, pre-frozen at -40℃ for 2 h, then transferred to a liquid nitrogen environment at -196℃, freeze-dried for 48 h, and finally pretreated at 500℃ for 2 h under Ar inert atmosphere, and then heat treated at 1000℃ for 3 h. This process first forms a fiber structure with Si3N4-C as the core and alumina as the shell, which has significantly better mechanical strength and high temperature resistance than single fibers. When the crack encounters the core-shell fiber, it will deflect or be forced to bypass the fiber, consuming more energy. The alumina shell forms a dense oxide layer at high temperature, preventing oxygen from diffusing to the core layer and delaying the oxidation and decomposition of Si3N4. The core-shell fiber forms Si-O-Si or Si-O-Al covalent bonds at the contact points through heat treatment, enhancing the stability of the aerogel. The Si3N4-C@Al2O3 core-shell fiber aerogel is obtained;
[0036] S2, grinding the Si3N4-C@Al2O3 core-shell fiber aerogel prepared in step S1 for 40 s, adding the silica-coated modified boron nitride and resin composite phase change microcapsules and nano yttrium oxide into 100 mL of anhydrous ethanol, ultrasonic dispersion for 30 min, adding polyvinyl butyral, stirring for 2 h, freeze-drying, and then loading the obtained powder into a mold, cold pressing at 50 MPa, isostatic pressing at 300 MPa to shape, and then treating the blank in an Ar / N2 inert atmosphere at 600 ℃ for 2 h and then at 1600 ℃ for 3 h, wherein the volume ratio of Ar and N2 is 9:1, the silica-coated modified boron nitride and resin composite phase change microcapsules are attached to the surface of the Si3N4-C@Al2O3 core-shell fiber aerogel, and the two are initially connected and fixed by van der Waals force and mechanical interlocking, the Si3N4-C@Al2O3 core-shell fiber aerogel serves as a matrix skeleton, and the silica-coated modified boron nitride and resin composite phase change microcapsules serve as a reinforcing phase, after sintering, the carbonized residues of the resin shell layer form chemical bonds with Si3N4 at the interface, further enhancing the interfacial bonding strength and reducing phase separation, polyvinyl butyral acts as a binder and forms a local coating film at the fiber-microcapsule interface, and nano yttrium oxide reacts with Si3N4 and Al2O3 to form Y-Si-Al-O-N glass phase, filling the grain boundary pores and improving the density, to obtain a silicon nitride ceramic matrix composite material.
[0037] In this embodiment, scanning electron microscopy is performed on the prepared silicon nitride ceramic matrix composite material to observe its micro-morphology, Figure 1 The SEM image of the silicon nitride ceramic matrix composite material prepared in Example 1 is magnified 1000 times, as shown in Figure 1 The silicon nitride ceramic matrix composite material prepared in this embodiment has a fiber morphology and good interfacial bonding.
[0038] Example 2
[0039] This embodiment proposes a silicon nitride ceramic matrix composite material, which comprises the following components by weight: 10 parts of silica-coated modified boron nitride and resin composite phase change microcapsules, 50 parts of Si3N4-C@Al2O3 core-shell fiber aerogel, 8 parts of nano yttrium oxide, and 5 parts of polyvinyl butyral.
[0040] The silica-coated modified boron nitride and resin composite phase change microcapsules are made from the following components by weight: 2 parts of hydroxylated boron nitride, 30 parts of pentaerythritol paraffin blend, 10 parts of resin prepolymer solution, 8 parts of complex emulsifier, 3 parts of silica sol, 5 parts of hydrogen peroxide, and 1 part of 3-glycidyl ether oxypropyl trimethoxysilane.
[0041] The preparation method of the silica-coated modified boron nitride and resin composite phase change microcapsules specifically includes the following steps:
[0042] (1) Put 8.0 g of boron nitride and 4.0 g of glucose into a ball mill jar, with a material-to-ball ratio of 1:5, and fix the ball mill jar in a planetary ball mill, and mill at a speed of 400 rpm for 10 h. The ball-milled product is placed in deionized water, and ultrasonically dispersed at a power of 200 W for 20 min. First, centrifuge at a low speed of 1000 rpm for 5 min, and then centrifuge the upper clear liquid at a high speed of 9000 rpm for 10 min. Collect the precipitate, and perform suction filtration, ethanol washing, and vacuum freeze-drying. The hydroxylated boron nitride has a hydrophilic group on the surface, and can be better dispersed in water or a polar solvent, avoiding the agglomeration problem of traditional boron nitride in ceramic slurry. The uniform dispersion of the hydroxylated boron nitride sheet layer can hinder crack propagation, improve the fracture toughness of the ceramic through crack deflection and bridging mechanisms, and more easily form a heat-conducting network in the ceramic, improving the high-temperature resistance. Hydroxylated boron nitride is obtained;
[0043] (2) Add 0.8 g of melamine, 1.0 g of urea, and 2.0 g of formaldehyde solution to 30 mL of deionized water, adjust the pH to 8.0 using a 5% mass fraction of triethanolamine solution, and stir at 60°C for 40 min to obtain a resin prepolymer solution. Dissolve 1 mL of 3-glycidyloxypropyltrimethoxysilane in 15 mL of a 50% mass fraction of ethanol solution, adjust the pH to 5.0 with acetic acid, and pre-hydrolyze for 20 min. Then, weigh 0.2 g of the hydroxylated boron nitride obtained in step (1) into the hydrolysis solution, ultrasonically disperse at a power of 100 W for 10 min, adjust the pH to 8.5 with a 10% mass fraction of triethanolamine solution, and finally add to the resin prepolymer solution. A high-performance resin prepolymer solution is prepared by modifying the hydroxylated boron nitride composite with melamine-urea-formaldehyde resin and silane coupling agent. The nanosheet structure of the hydroxylated boron nitride can form a reinforcing network in the resin, improving the mechanical strength of the composite material and reducing the dimensional change of the resin at high temperatures. The 3-glycidyloxypropyltrimethoxysilane enhances the interfacial bonding force between the hydroxylated boron nitride and the resin, reducing the risk of phase separation. A resin prepolymer solution containing modified boron nitride is obtained;
[0044] (3) 3.0 g of pentaerythritol paraffin blend, 0.8 g of a compound emulsifier, and 30 mL of deionized water were added to a 250 mL three-necked flask, the mass ratio of pentaerythritol and paraffin in the pentaerythritol paraffin blend was 70:30, pentaerythritol acted as a high-melting-point polyol, which could enhance the skeleton support of paraffin and reduce the risk of deformation during degreasing, paraffin and pentaerythritol could widen the temperature control range of ceramic materials, and as phase change energy storage materials, they could enhance the high temperature resistance, the compound emulsifier was composed of Span 80 and Tween 60, the mass ratio of the two was 3:1, after complete melting at 50°C, the resin prepolymer solution containing modified boron nitride in step (2) was added, and emulsification treatment was carried out at a speed of 15000 rpm for 20 min, ice bath cooling treatment was adopted during emulsification, the obtained oil-in-water emulsion was transferred to a 500 mL three-necked flask, a 5% triethanolamine solution was added under the stirring speed of 300 rpm to adjust the pH to 8.5, 10 min later, a 10% citric acid solution was slowly added through a constant pressure dropping funnel, the pH was adjusted to 4.5, then the temperature was raised to 60°C at a rate of 0.5°C / min, 0.1 g of sodium chloride was added, and the reaction was carried out for 0.5 h, then the temperature was raised to 80°C and the reaction was carried out for 1 h, finally, the pH was adjusted to 7.0 by sodium hydroxide solution to terminate the reaction, the obtained suspension was sieved and suction filtered, and then washed with 60°C deionized water and anhydrous ethanol for 3 times, the precipitate was vacuum dried, the hydroxylated boron nitride was embedded in the melamine-urea-formaldehyde co-condensation resin to form a dense thermosetting resin material as a wall material to coat the core material of the pentaerythritol paraffin blend, the hydroxylated boron nitride nanosheet formed a brick structure in the resin shell layer, when the crack propagated, the hydroxylated boron nitride sheet layer forced the crack to bypass or branch, at the same time, the plastic deformation of the resin could absorb energy, and the urea segment in the resin also provided flexibility, thus improving the risk of brittle fracture, the core material could absorb thermal stress when the temperature changed, and could also reduce the initiation of internal microcracks of the ceramic, the inert protection of the hydroxylated boron nitride and the synergistic effect of the resin carbonization network improved the high temperature stability of the ceramic material, and a modified boron nitride and resin composite phase change microcapsule was obtained;
[0045] (4) 1 mL of tetraethyl orthosilicate and 7 mL of anhydrous ethanol were mixed and magnetically stirred for 10 min, then 1 mL of deionized water and 0.05 mL of ammonia water were slowly added, and stirred at 30°C water bath for 1 h to obtain silica sol for standby. The modified boron nitride and resin composite phase change microcapsules described in step (3) were dispersed in 50 mL of 60°C deionized water, and 3 mL of 15% hydrogen peroxide liquid was added. Hydrogen peroxide can oxidize the residual organic matter on the surface of the microcapsules, exposing more hydroxyl groups and enhancing the interfacial bonding with the silica sol. Ultrasonic treatment for 10 min, suction filtration, the product was washed with anhydrous ethanol 3 times, vacuum drying, to obtain modified boron nitride and resin composite phase change microcapsule pretreated powder, for standby, then the modified boron nitride and resin composite phase change microcapsule pretreated powder was dispersed in 50 mL of anhydrous ethanol, ultrasonic treatment for 20 min, then the silica sol was added to the dispersion at a rate of 1 mL / min, while maintaining magnetic stirring at 30°C and 800 rpm for 10 h. Finally, centrifugation, the collected precipitate was washed with anhydrous ethanol 3 times, supercritical CO2 drying, hydrogen peroxide pretreatment of modified boron nitride and resin composite phase change microcapsules can ensure the stability of the silica coating layer deposited on the surface of the microcapsules, which is beneficial to the coating layer to better enhance the mechanical strength and chemical inertness of the microcapsules, and at the same time, enhance the compatibility with the ceramic matrix. The structural characteristics of the microcapsules can locally deform plastically under stress, absorbing impact energy and improving the fracture toughness of the material. The flexibility of the resin and the rigidity of the silica form a soft-hard alternating structure with toughening effect. The high temperature resistance of silica can isolate oxygen and prevent the decomposition of resin at high temperature, while blocking the volatilization of paraffin. The high thermal conductivity of hydroxylated boron nitride can accelerate heat diffusion, avoid local overheating, and delay the high temperature oxidation of the ceramic matrix. The silica-coated modified boron nitride and resin composite phase change microcapsules were obtained.
[0046] The embodiment provides a preparation method of a silicon nitride ceramic matrix composite material, specifically comprising the following steps:
[0047] S1, 2.0 g of polyacrylonitrile, 0.8 g of polysilazane, 0.3 g of basic aluminum acetate and 0.1 g of polyvinylpyrrolidone were dissolved in 10 mL of N,N-dimethylformamide solvent, stirred for 10 h to form a core layer solution for standby, 0.5 g of polyvinylpyrrolidone was dissolved in 10 mL of 70% ethanol solution, stirred for 3 h, 0.3 g of 10 nm particle size of alumina particles was slowly added, first ultrasonic dispersion for 20 min at 200 W power, then aluminum nitrate nonahydrate was added, the amount of aluminum nitrate nonahydrate added was 0.1 g, and the active alumina was generated by high temperature decomposition of aluminum nitrate nonahydrate, which together with the original nano-alumina particles formed a ceramic phase, improving the uniformity, continuity of the shell layer, enhancing the mechanical strength and high temperature resistance, and also filling the gap between the fibers, and forming chemical bonding with the core layer material through high temperature sintering, improving the bonding of the core-shell interface, effectively reducing stress concentration and improving toughness, then magnetic stirring for 3 h to form a shell layer solution for standby, then using coaxial electrospinning technology, the core layer solution was filled into a 21G inner needle, and the shell layer solution was filled into a 16G outer needle, the core layer solution was pushed at a speed of 0.006 mL / min and a voltage of +16 kV, the shell layer solution was pushed at a speed of 0.01 mL / min and a voltage of -6 kV, and the receiving distance was 18 cm, and the prepared core-shell precursor nanofiber was collected in a 50℃ oven for 0.5 h, then the temperature was increased to 280℃ at a rate of 5℃ / min and kept for 2 h, the dried product was ground and dispersed in 50 mL of 50% ethanol solution, pre-frozen at -40℃ for 1 h, then transferred to a liquid nitrogen environment at -196℃, and freeze-dried for 24 h, finally pretreated at 500℃ for 1 h under Ar inert atmosphere, and then heat treated at 800℃ for 2 h, this process first forms a fiber structure with Si3N4-C as the core and alumina as the shell, which has better mechanical strength and high temperature resistance than single fiber, when the crack meets the core-shell fiber, it will deflect or be forced to bypass the fiber, consuming more energy, the alumina shell forms a dense oxide layer at high temperature, preventing oxygen from diffusing to the core layer, delaying the oxidation and decomposition of Si3N4, and then through freeze-drying and heat treatment, a three-dimensional porous network aerogel based on core-shell fiber is formed, the core-shell fiber forms Si-O-Si or Si-O-Al covalent bond at the contact point through heat treatment, enhancing the stability of the aerogel, and obtaining Si3N4-C@Al2O3 core-shell fiber aerogel;
[0048] S2, grinding the Si3N4-C@Al2O3 core-shell fiber aerogel of step S1 for 30 s, adding the silica-coated modified boron nitride and resin composite phase change microcapsules and nano yttrium oxide into 100 mL of anhydrous ethanol, ultrasonic dispersion for 20 min, adding polyvinyl butyral, stirring for 1 h, freeze-drying, the obtained powder is loaded into a mold, cold pressing at 20 MPa, isostatic pressing at 200 MPa for shaping, and then the embryo is treated at 300 ℃ for 1 h and then at 1400 ℃ for 2 h in an Ar / N2 inert atmosphere, wherein the volume ratio of Ar and N2 is 9:1, the silica-coated modified boron nitride and resin composite phase change microcapsules are attached to the surface of the Si3N4-C@Al2O3 core-shell fiber aerogel, and the two are initially connected and fixed by van der Waals force and mechanical interlocking, the Si3N4-C@Al2O3 core-shell fiber aerogel serves as a matrix skeleton, the silica-coated modified boron nitride and resin composite phase change microcapsules serve as a reinforcing phase, after sintering, the carbonized residues of the resin shell layer form chemical bonds with Si3N4 at the interface, further enhancing the interfacial bonding strength and reducing phase separation, polyvinyl butyral acts as a binder and forms a local coating film at the fiber-microcapsule interface, nano yttrium oxide reacts with Si3N4 and Al2O3 to form Y-Si-Al-O-N glass phase, filling the grain boundary pores and improving the density, and a silicon nitride ceramic matrix composite is obtained.
[0049] Example 3
[0050] The present embodiment provides a silicon nitride ceramic matrix composite, which comprises the following components by weight: 12.5 parts of silica-coated modified boron nitride and resin composite phase change microcapsules, 55 parts of Si3N4-C@Al2O3 core-shell fiber aerogel, and 9 parts of nano yttrium oxide, and 6.5 parts of polyvinyl butyral.
[0051] The silica-coated modified boron nitride and resin composite phase change microcapsules are made from the following components by weight: 4 parts of hydroxylated boron nitride, 35 parts of pentaerythritol paraffin blend, 15 parts of resin prepolymer solution, 9 parts of compound emulsifier, 4 parts of silica sol, 6.5 parts of hydrogen peroxide, and 2 parts of 3-glycidyl ether oxypropyl trimethoxysilane.
[0052] The preparation method of the silica-coated modified boron nitride and resin composite phase change microcapsules specifically includes the following steps:
[0053] (1) Put 9.0 g of boron nitride and 4.5 g of glucose into a ball mill jar, with a material-to-ball ratio of 1:5, and fix the ball mill jar in a planetary ball mill, and mill at a speed of 450 rpm for 11 h. The ball-milled product is placed in deionized water, and ultrasonic dispersion is performed at a power of 300 W for 25 min. First, low-speed centrifugation is performed at 1500 rpm for 7.5 min, and then high-speed centrifugation is performed at 9500 rpm for 15 min. The collected precipitate is subjected to suction filtration, ethanol washing, and vacuum freeze-drying. The hydroxylated boron nitride has a hydrophilic group on the surface, can be better dispersed in water or a polar solvent, avoids the agglomeration problem of traditional boron nitride in ceramic slurry, and can hinder crack propagation by uniformly dispersing the hydroxylated boron nitride sheet layer, thereby improving the fracture toughness of the ceramic through crack deflection and bridging mechanisms, and also more easily forming a heat-conducting network in the ceramic to improve high-temperature resistance. Hydroxylated boron nitride is obtained;
[0054] (2) Add 0.9 g of melamine, 1.5 g of urea, and 2.5 g of formaldehyde solution to 30 mL of deionized water, adjust the pH to 8.3 using a 5% mass fraction of triethanolamine solution, stir at 65°C for 45 min, and obtain a resin prepolymer solution for later use. Dissolve 2 mL of 3-glycidyloxypropyltrimethoxysilane in 15 mL of a 60% mass fraction of ethanol solution, adjust the pH to 5.5 with acetic acid, and pre-hydrolyze for 25 min. Then, weigh 0.4 g of the hydroxylated boron nitride described in step (1) and add it to the hydrolysis solution, ultrasonically disperse at a power of 150 W for 15 min, adjust the pH to 8.8 with a 10% mass fraction of triethanolamine solution, and finally add it to the resin prepolymer solution. A high-performance resin prepolymer solution is prepared by modifying the hydroxylated boron nitride composite with melamine-urea-formaldehyde resin and silane coupling agent. The nanosheet structure of the hydroxylated boron nitride can form a reinforcing network in the resin, improving the mechanical strength of the composite material and reducing the dimensional change of the resin at high temperatures. The 3-glycidyloxypropyltrimethoxysilane enhances the interfacial bonding force between the hydroxylated boron nitride and the resin, reducing the risk of phase separation. A resin prepolymer solution containing modified boron nitride is obtained;
[0055] (3) 3.5 g of pentaerythritol paraffin blend, 0.9 g of compound emulsifier and 40 mL of deionized water were added into a 250 mL three-necked flask, the mass ratio of pentaerythritol and paraffin in the pentaerythritol paraffin blend was 70:30, pentaerythritol acted as a high melting point polyol, which could enhance the skeleton support of paraffin and reduce the risk of deformation during degreasing, paraffin and pentaerythritol could widen the temperature control range of ceramic materials after blending, and as phase change energy storage materials, they could enhance the high temperature resistance by regulating the thermal performance, the compound emulsifier was composed of span 80 and tween 60, the mass ratio of the two was 3:1, after complete melting at 50°C, the resin prepolymer solution containing modified boron nitride in step (2) was added, and emulsification treatment was carried out at a speed of 16500 rpm for 25 min, ice bath cooling treatment was adopted during emulsification, the obtained oil-in-water emulsion was transferred to a 500 mL three-necked flask, 5% triethanolamine solution was added under the stirring speed of 350 rpm to adjust the pH to 8.5, 15 min later, 10% citric acid solution was slowly added through a constant pressure dropping funnel to adjust the pH to 4.8, then the temperature was raised to 60°C at a rate of 0.5°C / min, 0.2 g of sodium chloride was added, and the reaction was carried out for 0.75 h, then the temperature was raised to 80°C and the reaction was carried out for 1.5 h, finally, sodium hydroxide solution was used to adjust the pH to 7.0 to terminate the reaction, the obtained suspension was sieved and suction filtered, and then washed with 60°C deionized water and anhydrous ethanol for 4 times respectively, the precipitate was vacuum dried, the hydroxylated boron nitride embedded in the melamine-urea-formaldehyde co-condensation resin formed a dense thermosetting resin material as a wall material to coat the core material of pentaerythritol paraffin blend, the hydroxylated boron nitride nanosheet formed a brick structure in the resin shell layer, when the crack propagated, the hydroxylated boron nitride sheet layer forced the crack to bypass or branch, at the same time, the plastic deformation of the resin could absorb energy, and the urea segment in the resin also provided flexibility, thus improving the risk of brittle fracture, the core material could absorb thermal stress when the temperature changed, which could also reduce the initiation of internal microcracks of ceramic, the inert protection of hydroxylated boron nitride and the synergistic effect of resin carbonization network improved the high temperature stability of ceramic materials, and modified boron nitride and resin composite phase change microcapsules were obtained;
[0056] (4) mixing 1.5 mL of tetraethyl orthosilicate and 7.5 mL of anhydrous ethanol, magnetically stirring for 15 min, then slowly adding 1.5 mL of deionized water and 0.08 mL of ammonia water, stirring in a 35°C water bath for 1.5 h to obtain a silica sol for standby, dispersing the modified boron nitride and resin composite phase change microcapsules in step (3) in 50 mL of 60°C deionized water, adding 4 mL of 15% hydrogen peroxide liquid, the hydrogen peroxide can oxidize the organic matter remaining on the surface of the microcapsules, exposing more hydroxyl groups and enhancing the interfacial bonding with the silica sol, ultrasonic treatment for 12.5 min, suction filtration, washing the product with anhydrous ethanol 4 times, vacuum drying to obtain modified boron nitride and resin composite phase change microcapsule pretreated powder for standby, then dispersing the modified boron nitride and resin composite phase change microcapsule pretreated powder in 50 mL of anhydrous ethanol, ultrasonic treatment for 25 min, then adding the silica sol to the dispersion at a rate of 1 mL / min while maintaining magnetic stirring at 32.5°C and 900 rpm for 11 h, finally centrifuging, washing the collected precipitate with anhydrous ethanol 4 times, and supercritical CO2 drying, the oxidation pretreatment of the modified boron nitride and resin composite phase change microcapsule by hydrogen peroxide can ensure the stable loading of the silica coating layer deposited on the surface of the microcapsule, which is conducive to the coating layer to better enhance the mechanical strength and chemical inertness of the microcapsule, and to enhance the compatibility with the ceramic matrix, the structure of the microcapsule can locally deform plastically under stress, absorbing impact energy and improving the fracture toughness of the material, wherein the flexibility of the resin and the rigidity of the silica form a soft-hard alternating structure with toughening effect, the high temperature resistance of the silica can isolate oxygen to prevent the resin from decomposing at high temperature, and also block the volatilization of paraffin, the high thermal conductivity of the hydroxylated boron nitride can accelerate heat diffusion, avoid local overheating, and delay the high temperature oxidation of the ceramic matrix, to obtain silica-coated modified boron nitride and resin composite phase change microcapsules.
[0057] The embodiment provides a preparation method of a silicon nitride ceramic matrix composite material, and specifically comprises the following steps:
[0058] S1, 2.25 g of polyacrylonitrile, 0.9 g of polysilazane, 0.35 g of basic aluminum acetate and 0.15 g of polyvinylpyrrolidone were dissolved in 10 mL of N,N-dimethylformamide solvent, stirred for 11 h to form a core layer solution for standby, 0.75 g of polyvinylpyrrolidone was dissolved in 10 mL of 70% ethanol solution, stirred for 3.5 h, 0.4 g of 15 nm particle size of alumina particles was slowly added, first ultrasonic dispersion at 200 W power for 25 min, then aluminum nitrate nonahydrate was added, the amount of aluminum nitrate nonahydrate added was 0.15 g, and the active alumina was generated by high temperature decomposition of aluminum nitrate nonahydrate, which together with the original nano-alumina particles formed a ceramic phase, which improved the uniformity, continuity of the shell layer, enhanced the mechanical strength and high temperature resistance, and also filled the gap between the fibers, and formed a chemical bond with the core layer material through high temperature sintering, improved the bonding of the core-shell interface, effectively reduced stress concentration, improved toughness, and then magnetic stirring for 3.5 h to form a shell layer solution for standby. Then, using the coaxial electrospinning technology, the core layer solution was filled into the 21G inner needle, and the shell layer solution was filled into the 16G outer needle, the core layer solution was pushed at a speed of 0.007 mL / min and a voltage of +17 kV, the shell layer solution was pushed at a speed of 0.015 mL / min and a voltage of -4 kV, and the receiving distance was 19 cm. The prepared core-shell precursor nanofiber was collected and treated in a 55°C oven for 0.75 h, then the temperature was increased to 290°C at a rate of 5°C / min and kept for 2.5 h, the dried product was ground and dispersed in 50 mL of 50% ethanol solution, pre-frozen at -40°C for 1.5 h, then transferred to a liquid nitrogen environment at -196°C, and freeze-dried for 36 h. Finally, under Ar inert atmosphere, pretreatment at 500°C for 1.5 h, then heat treatment at 900°C for 2.5 h. This process first forms a fiber structure with Si3N4-C as the core and alumina as the shell, which has significantly better mechanical strength and high temperature resistance than single fiber. When the crack encounters the core-shell fiber, it will deflect or be forced to bypass the fiber, consuming more energy. The alumina shell forms a dense oxide layer at high temperature, preventing oxygen from diffusing to the core layer and delaying the oxidation and decomposition of Si3N4. The core-shell fiber forms Si-O-Si or Si-O-Al covalent bonds at the contact points through heat treatment, enhancing the stability of the aerogel. The Si3N4-C@Al2O3 core-shell fiber aerogel is obtained.
[0059] S2, grinding the Si3N4-C@Al2O3 core-shell fiber aerogel of step S1 for 35 s, and then mixing the Si3N4-C@Al2O3 core-shell fiber aerogel, the silica-coated modified boron nitride and resin composite phase change microcapsules, and nano yttrium oxide into 100 mL of anhydrous ethanol, ultrasonic dispersion for 25 min, adding polyvinyl butyral, stirring for 1.5 h, freeze-drying, and then loading the obtained powder into a mold, cold pressing at 35 MPa, and isostatic pressing at 250 MPa to shape, and then treating the blank in an Ar / N2 inert atmosphere at 450 ℃ for 1.5 h, and then at 1500 ℃ for 2.5 h, wherein the volume ratio of Ar and N2 is 9:1, the silica-coated modified boron nitride and resin composite phase change microcapsules are attached to the surface of the Si3N4-C@Al2O3 core-shell fiber aerogel, and the two are initially connected and fixed by van der Waals force and mechanical interlocking, the Si3N4-C@Al2O3 core-shell fiber aerogel serves as a matrix skeleton, the silica-coated modified boron nitride and resin composite phase change microcapsules serve as a reinforcing phase, after sintering, the carbonized residues of the resin shell layer form chemical bonds with Si3N4 at the interface, further enhancing the interfacial bonding strength and reducing phase separation, polyvinyl butyral serves as a binder and forms a local coating film at the fiber-microcapsule interface, and nano yttrium oxide reacts with Si3N4 and Al2O3 to form Y-Si-Al-O-N glass phase, filling the grain boundary pores and improving the density, thereby obtaining a silicon nitride ceramic matrix composite material.
[0060] Example 4
[0061] The present embodiment provides a silicon nitride ceramic matrix composite material, which comprises the following components in parts by weight: 15 parts of silica-coated modified boron nitride and resin composite phase change microcapsules, 50 parts of Si3N4-C@Al2O3 core-shell fiber aerogel, and 10 parts of nano yttrium oxide, and 8 parts of polyvinyl butyral.
[0062] The silica-coated modified boron nitride and resin composite phase change microcapsules are prepared from the following components in parts by weight: 2 parts of hydroxylated boron nitride, 40 parts of pentaerythritol paraffin blend, 20 parts of resin prepolymer solution, 10 parts of compound emulsifier, 5 parts of silica sol, 5 parts of hydrogen peroxide, and 1 part of 3-glycidyl ether oxypropyl trimethoxysilane.
[0063] The preparation method of the silica-coated modified boron nitride and resin composite phase change microcapsules specifically comprises the following steps:
[0064] (1) Put 10.0 g of boron nitride and 5.0 g of glucose into a ball mill jar, with a material-to-ball ratio of 1:5, and fix the ball mill jar in a planetary ball mill, and mill at a speed of 500 rpm for 10 h. The ball-milled product is placed in deionized water, and ultrasonically dispersed at a power of 400 W for 20 min. First, centrifuge at a low speed of 2000 rpm for 5 min, and then centrifuge the upper clear liquid at a high speed of 10000 rpm for 10 min. Collect the precipitate, and perform suction filtration, ethanol washing, and vacuum freeze-drying. The hydroxylated boron nitride has a hydrophilic group on the surface, and can be better dispersed in water or a polar solvent, avoiding the agglomeration problem of traditional boron nitride in ceramic slurry. The uniform dispersion of the hydroxylated boron nitride sheet layer can hinder crack propagation, improve the fracture toughness of the ceramic through crack deflection and bridging mechanisms, and more easily form a heat-conducting network in the ceramic, improving the high-temperature resistance. Hydroxylated boron nitride is obtained;
[0065] (2) Add 1.0 g of melamine, 2.0 g of urea, and 3.0 g of formaldehyde solution to 30 mL of deionized water, adjust the pH to 8.0 using a 5% mass fraction of triethanolamine solution, and stir at 70°C for 40 min to obtain a resin prepolymer solution. Dissolve 1 mL of 3-glycidyloxypropyltrimethoxysilane in 15 mL of a 70% mass fraction of ethanol solution, adjust the pH to 5.0 with acetic acid, and pre-hydrolyze for 20 min. Then, weigh 0.2 g of the hydroxylated boron nitride obtained in step (1) into the hydrolysis solution, ultrasonically disperse at a power of 200 W for 10 min, adjust the pH to 8.5 with a 10% mass fraction of triethanolamine solution, and finally add to the resin prepolymer solution. A high-performance resin prepolymer solution is prepared by modifying the hydroxylated boron nitride composite with melamine-urea-formaldehyde resin and silane coupling agent. The nanosheet structure of the hydroxylated boron nitride can form a reinforcing network in the resin, improving the mechanical strength of the composite material and reducing the dimensional change of the resin at high temperatures. The 3-glycidyloxypropyltrimethoxysilane enhances the interfacial bonding force between the hydroxylated boron nitride and the resin, reducing the risk of phase separation. A resin prepolymer solution containing modified boron nitride is obtained;
[0066] (3) 4.0 g of pentaerythritol paraffin blend, 1.0 g of a compounded emulsifier, and 50 mL of deionized water were added to a 250 mL three-necked flask, the mass ratio of pentaerythritol and paraffin in the pentaerythritol paraffin blend was 70:30, pentaerythritol acted as a high-melting-point polyol and could enhance the skeleton support of paraffin, reducing the risk of deformation during the defatting process, paraffin and pentaerythritol could widen the temperature control range of ceramic materials, and as phase change energy storage materials, they could enhance the high temperature resistance by regulating the thermal performance, the compounded emulsifier was composed of Span 80 and Tween 60, the mass ratio of the two was 3:1, after complete melting at 50°C, the resin prepolymer solution containing modified boron nitride described in step (2) was added, and emulsification treatment was carried out at a speed of 18000 rpm for 20 min, ice bath cooling treatment was adopted during the emulsification process, the obtained oil-in-water emulsion was transferred to a 500 mL three-necked flask, a 5% triethanolamine solution was added under the stirring speed of 400 rpm to adjust the pH to 8.5, 10 min later, a 10% citric acid solution was slowly added through a constant pressure dropping funnel, the pH was adjusted to 4.5, then the temperature was raised to 60°C at a rate of 0.5°C / min, 0.3 g of sodium chloride was added, and the reaction was carried out for 0.5 h, then the temperature was raised to 80°C and the reaction was carried out for 1 h, finally, the pH was adjusted to 7.0 by sodium hydroxide solution to terminate the reaction, the obtained suspension was sieved and suction filtered, and then washed with 60°C deionized water and anhydrous ethanol for 5 times, respectively, the precipitate was vacuum dried, the hydroxylated boron nitride was embedded in the melamine-urea-formaldehyde co-condensation resin to form a dense thermosetting resin material as a wall material to coat the core material of the pentaerythritol paraffin blend, the hydroxylated boron nitride nanosheet formed a brick structure in the resin shell layer, when the crack propagated, the hydroxylated boron nitride sheet layer forced the crack to bypass or branch, at the same time, the plastic deformation of the resin could absorb energy, and the urea segment in the resin also provided flexibility, thus improving the risk of brittle fracture, the core material underwent phase change when the temperature changed, absorbing thermal stress, which could also reduce the initiation of microcracks in the ceramic, the inert protection of the hydroxylated boron nitride and the synergistic effect of the resin carbonization network improved the high temperature stability of the ceramic material, and a modified boron nitride and resin composite phase change microcapsule was obtained;
[0067] (4) 2 mL of tetraethyl orthosilicate and 8 mL of anhydrous ethanol were mixed and magnetically stirred for 10 min, then 2 mL of deionized water and 0.1 mL of ammonia water were slowly added, and stirring was performed in a 40°C water bath for 1 h to obtain a silica sol for standby use. The modified boron nitride and resin composite phase change microcapsules described in step (3) were dispersed in 50 mL of deionized water at 60°C, and 3 mL of hydrogen peroxide liquid with a mass fraction of 15% was added. Hydrogen peroxide can oxidize the residual organic matter on the surface of the microcapsules, exposing more hydroxyl groups and enhancing the interfacial bonding with the silica sol. Ultrasonic treatment was performed for 10 min, and the product was washed with anhydrous ethanol for 5 times, and vacuum dried to obtain modified boron nitride and resin composite phase change microcapsule pretreated powder for standby use. Then, the modified boron nitride and resin composite phase change microcapsule pretreated powder was dispersed in 50 mL of anhydrous ethanol, and ultrasonic treatment was performed for 20 min. Then, the silica sol was added to the dispersion liquid at a rate of 1 mL / min, while maintaining magnetic stirring at 35°C and 1000 rpm for 1 h. Finally, centrifugation was performed, and the collected precipitate was washed with anhydrous ethanol for 5 times and supercritical CO2 dried. The oxidation pretreatment of the modified boron nitride and resin composite phase change microcapsule by hydrogen peroxide can ensure the stable loading of the silica coating layer deposited on the surface of the microcapsule, which is conducive to the coating layer to better improve the mechanical strength and chemical inertness of the microcapsule, and to enhance the compatibility with the ceramic matrix. The structural characteristics of the microcapsule can locally plastically deform under stress, absorb impact energy, and improve the fracture toughness of the material. The soft and hard alternating structure formed by the flexibility of the resin and the rigidity of the silica has a toughening effect. The high temperature resistance of the silica can isolate oxygen and prevent the resin from decomposing at high temperatures, while also blocking the volatilization of paraffin. The high thermal conductivity of the hydroxylated boron nitride can accelerate heat diffusion, avoid local overheating, and delay the high temperature oxidation of the ceramic matrix, thereby obtaining silica-coated modified boron nitride and resin composite phase change microcapsules.
[0068] The embodiment provides a preparation method of a silicon nitride ceramic matrix composite material, and specifically comprises the following steps:
[0069] S1, 2.5 g of polyacrylonitrile, 1.0 g of polysilazane, 0.4 g of basic aluminum acetate and 0.2 g of polyvinylpyrrolidone were dissolved in 10 mL of N,N-dimethylformamide solvent, stirred for 10 h to form a core layer solution for standby, 0.5 g of polyvinylpyrrolidone was dissolved in 10 mL of 70% ethanol solution, stirred for 3 h, 0.3 g of 20 nm particle size of alumina particles was slowly added, first ultrasonic dispersion for 20 min at 200 W power, then aluminum nitrate nonahydrate was added, the amount of aluminum nitrate nonahydrate added was 0.1 g, and the active alumina was generated by high temperature decomposition of aluminum nitrate nonahydrate, which together with the original nano-alumina particles formed a ceramic phase, improving the uniformity, continuity of the shell layer, enhancing the mechanical strength and high temperature resistance, and also filling the gap between the fibers, and forming chemical bonding with the core layer material through high temperature sintering, improving the bonding of the core-shell interface, effectively reducing stress concentration and improving toughness, then magnetic stirring for 3 h to form a shell layer solution for standby, then using coaxial electrospinning technology, the core layer solution was filled into a 21G inner needle, and the shell layer solution was filled into a 16G outer needle, the core layer solution was pushed at a speed of 0.008 mL / min and a voltage of +18kV, the shell layer solution was pushed at a speed of 0.01 mL / min and a voltage of -6kV, the receiving distance was 20 cm, and the prepared core-shell precursor nanofiber was collected in a 60℃ oven for 0.5 h, then the temperature was increased to 300℃ at a rate of 5℃ / min and kept for 2 h, the dried product was ground and dispersed in 50 mL of 50% ethanol solution, pre-frozen at -40℃ for 1 h, then transferred to a liquid nitrogen environment at -196℃, freeze-dried for 24 h, and finally pretreated at 500℃ for 1 h under Ar inert atmosphere, then heated to 1000℃ for 2 h. This process first forms a fiber structure with Si3N4-C as the core and alumina as the shell, which has significantly better mechanical strength and high temperature resistance than single fibers. When the crack encounters the core-shell fiber, it will deflect or be forced to bypass the fiber, consuming more energy. The alumina shell forms a dense oxide layer at high temperature, preventing oxygen from diffusing to the core layer and delaying the oxidation and decomposition of Si3N4. The core-shell fiber forms Si-O-Si or Si-O-Al covalent bonds at the contact points through freeze-drying and heat treatment, enhancing the stability of the aerogel. The Si3N4-C@Al2O3 core-shell fiber aerogel is obtained;
[0070] S2, grinding the Si3N4-C@Al2O3 core-shell fiber aerogel prepared in step S1 for 30 s, adding the silica-coated modified boron nitride and resin composite phase change microcapsules and nano yttrium oxide into 100 mL of anhydrous ethanol, ultrasonic dispersion for 20 min, adding polyvinyl butyral, stirring for 1 h, freeze-drying, and then loading the obtained powder into a mold, cold pressing at 20 MPa, and isostatic pressing at 200 MPa to shape, and then treating the green body in an Ar / N2 inert atmosphere at 600 ℃ for 1 h and then at 1600 ℃ for 2 h, wherein the volume ratio of Ar and N2 is 9:1, the silica-coated modified boron nitride and resin composite phase change microcapsules are attached to the surface of the Si3N4-C@Al2O3 core-shell fiber aerogel, and the two are initially connected and fixed by van der Waals force and mechanical interlocking, the Si3N4-C@Al2O3 core-shell fiber aerogel serves as a matrix skeleton, and the silica-coated modified boron nitride and resin composite phase change microcapsules serve as a reinforcing phase, after sintering, the carbonized residues of the decomposed resin shell layer form chemical bonds with Si3N4 at the interface, further enhancing the interfacial bonding strength and reducing phase separation, polyvinyl butyral acts as a binder and forms a local coating film at the fiber-microcapsule interface, nano yttrium oxide reacts with Si3N4 and Al2O3 to form Y-Si-Al-O-N glass phase, filling the grain boundary pores and improving the density, and a silicon nitride ceramic matrix composite is obtained.
[0071] Comparative Example 1
[0072] The present comparative example provides a silicon nitride ceramic matrix composite, which is different from Example 1 in that the silica-coated modified boron nitride and resin composite phase change microcapsules do not contain hydroxylated boron nitride; the preparation method of the silica-coated modified boron nitride and resin composite phase change microcapsules does not include step (1); and the preparation method of the silicon nitride ceramic matrix composite is the same as that of Example 1.
[0073] Comparative Example 2
[0074] The present comparative example provides a silicon nitride ceramic matrix composite, which is different from Example 1 in that the silica-coated modified boron nitride and resin composite phase change microcapsules do not contain silica sol and hydrogen peroxide; the preparation method of the silica-coated modified boron nitride and resin composite phase change microcapsules does not contain silica sol in step (4) and does not add hydrogen peroxide liquid; and the preparation method of the silicon nitride ceramic matrix composite is the same as that of Example 1.
[0075] Comparative Example 3
[0076] The comparative example provides a silicon nitride ceramic matrix composite, which is different from example 1 in that the Si3N4-C@Al2O3 core-shell fiber aerogel does not contain aluminum oxide and aluminum nitrate nonahydrate; the preparation method of the silica-coated modified boron nitride and resin composite phase change microcapsule is the same as that of example 1; and the preparation method of the silicon nitride ceramic matrix composite does not add aluminum oxide and aluminum nitrate nonahydrate in step S1, does not contain a shell layer solution, and uses a conventional electrostatic spinning technology.
[0077] Experimental example 1
[0078] Mechanical property experiment
[0079] Test sample: silicon nitride ceramic matrix composite prepared by examples 1-4 and comparative examples 1-3.
[0080] Test method: the test sample is determined by the single-edge notched beam method, processed into a sample size of 4.0x4.0x36.0mm, with a slot width of 0.2mm and a slot depth of 2mm, and the fracture toughness (MPa.m 1 / 2 ) is tested by the three-point bending method on a universal material testing machine (JITAIW50KN-JIMEC) with a test span of 30.0mm and a loading rate of 0.05mm / min. Three samples are selected for testing and the average value is taken.
[0081] Figure 2 The fracture toughness results of examples 1-4 and comparative examples 1-3 are shown in the figure. As shown in the figure, the fracture toughness of examples 1-4 is 14.9-15.9MPa.m 1 / 2 , indicating that the fracture toughness is good; the fracture toughness of comparative examples 1-3 is 8.2-10.7MPa.m 1 / 2 , indicating that the fracture toughness is general; the silica-coated modified boron nitride and resin composite phase change microcapsule of comparative example 1 does not contain hydroxylated boron nitride, which cannot hinder crack propagation through uniform dispersion of nanosheets in the resin, resulting in general fracture toughness; the silica-coated modified boron nitride and resin composite phase change microcapsule of comparative example 2 does not contain silica sol and hydrogen peroxide, which cannot coat silica on the surface of the microcapsule, increasing the risk of microcapsule rupture, and cannot form a soft-hard alternating structure with the resin, limiting the toughening effect, and cannot make the surface of the microcapsule present nano concave-convex, which is not conducive to mechanical combination with the ceramic substrate, resulting in general fracture toughness; the Si3N4-C@Al2O3 core-shell fiber aerogel of comparative example 3 does not contain aluminum oxide and aluminum nitrate nonahydrate, which cannot form core-shell fibers, and cannot consume more fracture energy through active particles decomposed by the shell layer aluminum oxide and aluminum nitrate nonahydrate, and is not conducive to promoting the increase of fiber pull-out work, resulting in general fracture toughness.
[0082] Experimental example 2
[0083] High temperature resistance experiment
[0084] Test sample: silicon nitride ceramic matrix composites prepared by examples 1-4 and comparative examples 1-3.
[0085] Test method: the test sample was made into a test sample size of 4.0x4.0x36.0mm, 10 test samples per group, and high temperature three-point bending test was carried out according to ASTM C1161, first, the bending strength (MPa) of each group of 5 test samples at room temperature was tested and the average value was taken, then another 5 test samples were installed in a high temperature three-point bending test machine (equipped with a high temperature furnace, a ceramic pressure head and a high temperature resistant clamp), inert gas (Ar) was introduced, the temperature was raised to 1500℃ at a rate of 5℃ / min, and the temperature was kept for 30min, by recording the load-displacement curve, the sampling frequency was ≥10Hz, the loading rate was 0.5mm / min, and the load dropped to the sample fracture as the termination condition, the load, displacement, temperature and time were recorded in real time, the bending strength (MPa) at 1500℃ was obtained, and the average value was taken, finally, the bending strength at 1500℃ and the bending strength at room temperature were taken as the high temperature strength retention rate (%).
[0086] Figure 3 The high temperature strength retention rate results of examples 1-4 and comparative examples 1-3 are shown in the figure; as shown in the figure, the high temperature strength retention rate of examples 1-4 is 57-63%, indicating good high temperature resistance; the high temperature strength retention rate of comparative examples 1-3 is 32-43%, indicating general high temperature resistance; the silicon dioxide coated modified boron nitride and resin composite phase change microcapsules in comparative example 1 do not contain hydroxylated boron nitride, which cannot embed the nanosheet layer into the resin carbonized network to play the role of inert protection, resulting in general high temperature resistance; the silicon dioxide coated modified boron nitride and resin composite phase change microcapsules in comparative example 2 do not contain silicon dioxide sol and hydrogen peroxide, which cannot form a protective coating on the microcapsules through the high temperature resistance barrier of silicon dioxide, increasing the risk of resin decomposition and paraffin evaporation, and also cannot mechanically combine the nanometer concave-convex on the surface of the microcapsules with the ceramic substrate, limiting the role of the reinforcing phase, resulting in general high temperature resistance; the Si3N4-C@Al2O3 core-shell fiber aerogel in comparative example 3 does not contain aluminum oxide and aluminum nitrate nonahydrate, which cannot inhibit the oxidation of Si3N4 through the shell layer protection, and further is not conducive to the formation of chemical bond connection with the carbonized residues of the resin shell layer decomposition, increasing the risk of phase separation, resulting in general high temperature resistance.
[0087] The above experimental results show that the mechanical properties and high temperature resistance of the examples 1-4 of the application are obviously better than those of the comparative examples 1-3, wherein the fracture toughness and high temperature resistance of the example 1 using the silica-coated modified boron nitride and resin composite phase change microcapsule and Si3N4-C@Al2O3 core-shell fiber aerogel are better, the silica-coated modified boron nitride and resin composite phase change microcapsule are stably attached to the surface of the Si3N4-C@Al2O3 core-shell fiber aerogel in a chemical bonding and mechanical interlocking manner, the interfacial bonding strength is enhanced, the risk of phase separation is reduced, the combination of the two is better, the fracture toughness is improved by fiber toughening, aerogel pores and microcapsule stress dispersion, the high temperature resistance is improved by the low thermal conductivity of the aerogel and the heat absorption of the microcapsule, the mechanical properties of the silicon nitride are significantly improved in multiple ways, and the high temperature resistance is effectively enhanced.
[0088] Although the embodiments of the application have been shown and described, it is to be understood that for the purpose of the present application, the changes, modifications, equivalents, substitutions and variations of the embodiments can be made by those skilled in the art without departing from the spirit and principles of the application.
[0089] The above describes the application and its embodiments, which is not restrictive, and the drawings only show one of the embodiments of the application, and the actual application is not limited thereto. In summary, if those skilled in the art are inspired by it, without departing from the spirit and principles of the application, they can not design similar ways and embodiments without creativity, which should belong to the protection scope of the application.
Claims
1. A silicon nitride ceramic matrix composite, characterized by: The silicon nitride ceramic matrix composite comprises the following components by weight: 10-15 parts of silica-coated modified boron nitride and resin composite phase change microcapsules, 50-60 parts of Si3N4-C@Al2O3 core-shell fiber aerogel, 8-10 parts of nano yttrium oxide, and 5-8 parts of polyvinyl butyral; the silica-coated modified boron nitride and resin composite phase change microcapsules are made of the following components by weight: 2-6 parts of hydroxylated boron nitride, 30-40 parts of pentaerythritol paraffin blend, 10-20 parts of resin prepolymer solution, 8-10 parts of compound emulsifier, 3-5 parts of silica sol, 5-8 parts of hydrogen peroxide, and 1-3 parts of 3-glycidyl ether oxypropyl trimethoxysilane.
2. A method of producing the silicon nitride ceramic matrix composite according to claim 1, characterized by: Specifically comprising the following steps: S1, 2.0-2.5g of polyacrylonitrile, 0.8-1.0g of polysilazane, 0.3-0.4g of basic aluminum acetate and 0.1-0.2g of polyvinylpyrrolidone are dissolved in 10mL N,N-dimethylformamide solvent, stirred for 10-12h to form a core layer solution for standby, 0.5-1.0g of polyvinylpyrrolidone is dissolved in 10mL of 70% ethanol solution, stirred for 3-4h, 0.3-0.5g of alumina particles with a particle size of 10-20nm is slowly added, first ultrasonic dispersion at 200W power for 20-30min, then add aluminum nitrate nonahydrate, and then magnetic stirring for 3-4h to form a shell layer solution for standby, then use coaxial electrospinning technology, the core layer solution is loaded into a 21G inner needle, the shell layer solution is loaded into a 16G outer needle, the core layer solution is pushed at a speed of 0.006-0.008mL / min and a voltage of +16kV to +18kV, the shell layer solution is pushed at a speed of 0.01-0.02mL / min and a voltage of -6kV to -2kV, the receiving distance is 18-20cm, and the prepared core-shell precursor nanofiber is collected in a 50-60℃ oven for 0.5-1h, then the temperature is increased to 280-300℃ at a rate of 5℃ / min and kept for 2-3h, the dried product is ground and dispersed in 50mL of 50% ethanol solution, pre-frozen at -40℃ for 1-2h, then transferred to a liquid nitrogen environment at -196℃, freeze-dried for 24-48h, and finally pretreated at 500℃ under Ar inert atmosphere for 1-2h, then heat treated at 800-1000℃ for 2-3h to obtain Si3N4-C@Al2O3 core-shell fiber aerogel; S2, grinding the Si3N4-C@Al2O3 core-shell fiber aerogel prepared in step S1 for 30-40 s, adding the modified boron nitride coated with silica and the resin composite phase change microcapsule and nano yttrium oxide into 100 mL of anhydrous ethanol, ultrasonic dispersion for 20-30 min, adding polyvinyl butyral, stirring for 1-2 h, freeze-drying, loading the obtained powder into a mold, cold pressing at 20-50 MPa, isostatic pressing at 200-300 MPa for shaping, and then treating the blank in an Ar / N2 inert atmosphere at 300-600 ℃ for 1-2 h and at 1400-1600 ℃ for 2-3 h, wherein the volume ratio of Ar to N2 is 9:1, to obtain a silicon nitride ceramic matrix composite material.
3. The method of manufacturing a silicon nitride ceramic matrix composite according to claim 2, characterized in that: In step S1, the addition amount of aluminum nitrate nonahydrate is 0.1-0.2 g.
4. The method of manufacturing a silicon nitride ceramic matrix composite according to claim 3, characterized in that: The preparation method of the modified boron nitride coated with silica and resin composite phase change microcapsule specifically includes the following steps: (1) placing 8.0-10.0 g of boron nitride and 4.0-5.0 g of glucose in a ball mill jar, with a material-to-ball ratio of 1:5, fixing the ball mill jar in a planetary ball mill, and ball milling at a speed of 400-500 rpm for 10-12 h, placing the ball milling product in deionized water, ultrasonic dispersion at a power of 200-400 W for 20-30 min, low-speed centrifugation at 1000-2000 rpm for 5-10 min, high-speed centrifugation at 9000-10000 rpm for 10-20 min on the upper clear liquid, and collecting the precipitate for suction filtration, ethanol washing, and vacuum freeze-drying to obtain hydroxylated boron nitride; (2) adding 0.8-1.0 g of melamine, 1.0-2.0 g of urea, and 2.0-3.0 g of formaldehyde solution to 30 mL of deionized water, adjusting the pH to 8.0-8.5 using a 5% triethanolamine solution, stirring at 60-70 ℃ for 40-50 min to obtain a resin prepolymer solution, dissolving 1-3 mL of 3-glycidyl ether oxypropyl trimethoxysilane in 15 mL of an ethanol solution with a mass fraction of 50-70%, adjusting the pH to 5.0-6.0 with acetic acid, pre-hydrolyzing for 20-30 min, then weighing 0.2-0.6 g of the hydroxylated boron nitride prepared in step (1) and adding it to the hydrolysis solution, ultrasonic dispersion at a power of 100-200 W for 10-20 min, adjusting the pH to 8.5-9.0 using a 10% triethanolamine solution, and finally adding it to the resin prepolymer solution to obtain a resin prepolymer solution containing modified boron nitride; (3) 3.0-4.0 g of pentaerythritol paraffin blend, 0.8-1.0 g of complex emulsifier and 30-50 mL of deionized water were added into a 250 mL three-necked flask, the complex emulsifier was composed of Span 80 and Tween 60, the mass ratio of the two was 3:1, after complete melting at 50°C, the modified boron nitride-containing resin prepolymer solution in step (2) was added, emulsification treatment was carried out at a speed of 15000-18000 rpm for 20-30 min, ice bath cooling treatment was adopted during the emulsification process, the obtained oil-in-water emulsion was transferred into a 500 mL three-necked flask, a 5% triethanolamine solution was added under the stirring speed of 300-400 rpm to adjust the pH to 8.5, 10-20 min later, a 10% citric acid solution was slowly added dropwise through a constant pressure dropping funnel to adjust the pH to 4.5-5.0, then the temperature was raised to 60°C at a rate of 0.5°C / min, 0.1-0.3 g of sodium chloride was added, the reaction was carried out for 0.5-1 h, then the temperature was raised to 80°C and the reaction was carried out for 1-2 h, finally the pH was adjusted to 7.0 by using sodium hydroxide solution to terminate the reaction, the obtained suspension was sieved and suction filtered, and was washed with 60°C deionized water and anhydrous ethanol for 3-5 times in sequence, the precipitate was vacuum dried to obtain modified boron nitride and resin composite phase change microcapsules; (4) 1-2 mL of tetraethyl orthosilicate and 7-8 mL of anhydrous ethanol were mixed, magnetic stirring was carried out for 10-20 min, then 1-2 mL of deionized water and 0.05-0.1 mL of ammonia water were slowly added, water bath stirring was carried out at 30-40°C for 1-2 h to obtain silica sol, the modified boron nitride and resin composite phase change microcapsules in step (3) were dispersed in 50 mL of 60°C deionized water, a 15% hydrogen peroxide liquid was added, ultrasonic treatment was carried out for 10-15 min, suction filtration was carried out, the product was washed with anhydrous ethanol for 3-5 times, vacuum drying was carried out to obtain modified boron nitride and resin composite phase change microcapsule pretreatment powder, then the modified boron nitride and resin composite phase change microcapsule pretreatment powder was dispersed in 50 mL of anhydrous ethanol, ultrasonic treatment was carried out for 20-30 min, then the silica sol was added dropwise to the dispersion liquid at a rate of 1 mL / min, while magnetic stirring was maintained at 30-35°C and a speed of 800-1000 rpm for 10-12 h, finally centrifugation was carried out, the collected precipitate was washed with anhydrous ethanol for 3-5 times, and supercritical CO2 drying was carried out to obtain silica-coated modified boron nitride and resin composite phase change microcapsules.
5. The method of manufacturing a silicon nitride ceramic matrix composite according to claim 4, characterized in that: In step (3), the mass ratio of pentaerythritol and paraffin in the pentaerythritol paraffin blend is 70:
30.
6. The method of manufacturing a silicon nitride ceramic matrix composite according to claim 5, characterized in that: In step (4), the amount of hydrogen peroxide liquid added is 3-5 mL.
Citation Information
Patent Citations
POSS / alumina composite ceramic aerogel fiber and preparation method thereof
CN111575832A
Phase change energy storage microcapsule as well as preparation method and application thereof
CN113025285A
Boron nitride and silicon dioxide composite ceramic aerogel and preparation method thereof
CN116425554A
Preparation method of modified silicon dioxide coated paraffin phase change nano microcapsule
CN118480332A
Ceramic gel phase change energy storage self-insulation structure and preparation method thereof
CN119143476A
Cited By
High-temperature solid heat storage material based on industrial solid waste, preparation method of high-temperature solid heat storage material and heat storage pile
CN121293951A
Electronic ceramic material and preparation method thereof
CN122233762A